2018
DOI: 10.3390/ijms19123995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ceramide De Novo Synthesis Affects Adipocytokine Secretion and Improves Systemic and Adipose Tissue Insulin Sensitivity

Abstract: Ceramide accumulation in muscle and in liver is implicated in the induction of insulin resistance. Much less in known about the role of ceramide in adipose tissue. The aim of the present study was to elucidate the role of ceramide in adipose tissue and to clarify whether lipids participate in the regulation of adipocytokine secretion. The experiments were performed on male Wistar rats divided into three groups: 1. Control, 2. fed high fat diet (HFD), and 3. fed HFD and treated with myriocin. Ceramide (Cer) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
3
32
0
2
Order By: Relevance
“…We found that HFD consumption led to insulin resistance, as evidenced by increased fasting glucose and insulin concentration, impaired glucose tolerance, reduced insulin responsiveness, an increase in HOMA-IR and decreased muscular glucose uptake compared to the control group. We have noticed a significant increase in plasma FFA concentration and a significant increase in all the studied lipid groups in nonsilenced muscle, which was in line with observations made by other research groups [ 1 , 2 , 3 , 4 , 5 , 7 , 19 , 26 ]. However, we wanted to find out how, under conditions of induced insulin resistance, reducing DAG content would affect the insulin pathway and whether it would improve muscle glucose uptake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that HFD consumption led to insulin resistance, as evidenced by increased fasting glucose and insulin concentration, impaired glucose tolerance, reduced insulin responsiveness, an increase in HOMA-IR and decreased muscular glucose uptake compared to the control group. We have noticed a significant increase in plasma FFA concentration and a significant increase in all the studied lipid groups in nonsilenced muscle, which was in line with observations made by other research groups [ 1 , 2 , 3 , 4 , 5 , 7 , 19 , 26 ]. However, we wanted to find out how, under conditions of induced insulin resistance, reducing DAG content would affect the insulin pathway and whether it would improve muscle glucose uptake.…”
Section: Discussionsupporting
confidence: 92%
“…In obese and T2D subjects, plasma free fatty acid (FFA) concentration is often elevated compared to lean, healthy counterparts [ 1 ]. An increased concentration of FFA was observed in skeletal muscles in animals fed HFD [ 2 , 3 , 4 , 5 , 6 , 7 ], in obese people [ 8 , 9 ] and T2D patients [ 10 ]. Plasma FFAs enter muscle cells by diffusion or via protein transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking ceramide production with SPT inhibitor myriocin in DIO mice led to increased levels of circulating high molecular weight adiponectin ( 59 ). This inverse relationship between adiponectin and ceramides has also been shown in rats ( 155 , 156 ) and dolphins.…”
Section: Preclinical Studies Of Adiponectin and Ceramidessupporting
confidence: 68%
“…In another study, myriocin prevented the development of IR in young db/db mice and reduced liver mass, without changes in body weight, visceral fat mass, locomotor activity and oxygen consumption [ 76 ]. More recently, Blachnio-Zabielska et al also reported a protective effect of myriocin on insulin sensitivity in HFD-fed rats [ 77 ]. Surprisingly, the treatment also reduced DAG content in subcutaneous and visceral fat depots.…”
Section: Causal Role Of Ceramides In Insulin Resistance?mentioning
confidence: 99%